Training Website Creation and Management for Efforts to Improve School Media Literacy at SMP Negeri 4 Bayongbong - Ardi Mulyana Haryadi; Zainah Asmaniah; Cecep Dudung Julianto; Ipan Ipan; Riawati Riawati (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract Sekolah Menengah Pertama Negeri (SMP N) 4 Bayongbong is a secondary school located in the Cilimus area, Bayongbong. Based on observations and interviews that have been conducted, there are problems at the school, namely regarding the lack of knowledge about media literacy and management of website content from teachers. The purpose of this activity is to provide training in website content creation and media literacy so that schools can independently manage the school website. The service activities are divided into several stages, namely need assessment, training on website content and media literacy, and follow-up to teachers of SMP N 4 Bayongbong. The result of this activity is that teachers can understand how to manage website content and get increased media literacy. Abstrak Sekolah Menengah Pertama Negeri (SMPN) 4 Bayongbong adalah sekolah lanjutan pertama yang berada di daerah Cilimus Bayongbong, Garut. Berdasarkan observasi serta wawancara yang telah dilakukan, terdapat permasalahan di Sekolah tersebut, yaitu mengenai kurangnya pengetahuan mengenai literasi media serta pengelolaan konten website dari para guru di sekolah tersebut. Tujuan kegiatan ini adalah memberikan pelatihan pembuatan konten website maupun literasi media agar sekolah dapat mandiri dalam mengelola website sekolah. Kegiatan pengabdian terbagi menjadi beberapa tahap, yaitu pengelompokan, pelatihan konten website dan literasi media, serta follow up kepada guru SMPN 4 Bayongbong. Hasil kegiatan ini adalah guru-guru dapat memahami mengenai cara pengelolaan konten website serta mendapatkan peningkatan literasi media.